Investigation of anti-cancer activity from Aquilaria Subintegra against MCF-7 breast cancer cells - Phirdaous bin Abbas (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Agarwood is the most valuable non-timber forest product originating from the Aquilaria species associated with traditional religious and medicinal purposes. Interestingly, agarwood has been reported to be used to treat inflammatory related diseases which include cancer. However, there is very limited scientific evidence on anti-cancer properties of plant materials from agarwood. Therefore, this present study aims to investigate the potential anti-cancer activity of agarwood plant material against MCF-7 breast cancer cells. Firstly, leaf and branch samples collected from the Aquilaria subintegra were cleaned prior to extraction process. Employing the solid to liquid extraction technique, solvent system and sample type selection was conducted to obtain extract with the highest anti-cancer activity in vitro. Results showed that branch type of sample and ethanol as solvent exhibited the highest anti-cancer activity thus, these two qualitative parameters were selected for the process conditions screening in the 24 full factorial design generated using MODDE software from SIMCA-P+ V12.0.1 to determine the most influential process conditions affecting the yield of agarwood branch extract (ABE). Parameters included in the design were temperature (ºC), time (hour), agitation speed (rpm), and ratio of sample to the solvent (g/ml). Experimental run 11 with 12 hours extraction time, 50 °C temperature, 100 rpm and 60 ml extraction volume gave the highest yield of 0.2130 ± 0.036 g/g of ABE. Modeling using the Partial Least Square (PLS) generated a model fit with the coefficient of determination (R2) value of 0.9591 and the goodness of prediction (Q2) value of 0.7355. Regression analysis found that agitation speed has the highest negative significant effect to the yield of crude extract. Temperature and temperature-volume coefficients were both positive significant effects In vitro anti-cancer screening assays were used to determine the potential cytotoxic effects of ABE against MCF-7 breast cancer cells and VERO normal kidney cells. At 100 µg/ml, ABE showed anti-attachment and cytotoxic effects on MCF-7 breast cancer cells. The lowest IC50 value of ABE against MCF-7 cells was 8 µg/ml obtained via the Sulforhodamine B (SRB) assay from the experimental run 16 (extraction time of 24 hours, 50 °C extraction temperature, agitation speed of 200 rpm and 60 ml solvent). ABE also showed cytotoxic effects on VERO normal kidney cells, however, this can only be observed at higher concentration (>64 µg/ml). Phytoconstituents screening showed that terpenoids, flavonoids and phenolics compounds are present in ABE, supporting the anti-cancer activities observed. Cytokinetics study on MCF-7 cells showed that run 16 ABE reduced the generation number from 3.52 to 1.22 and the growth rate from 0.0421 h-1 to 0.0158 h-1. Doubling time of MCF-7 was extended from 16.4 hours to 43.8 hours. In conclusion, ethanolic agarwood branch extract possess anti-cancer properties against breast cancer cells. As such, further studies are warranted to fully exploit the plant materials from agarwood tree as source of medicinal compounds.